Plasma technology rationalizes 2-component processes - Moritzer, Elmar; Mühlhoff, Frederik Marvin; Krampe, Erhard; Böhnke, Birte (adhesion ADHESIVES + SEALANTS)

Plasma-Technologie zur Rationalisierung von 2K-Prozessen - Moritzer, Elmar; Mühlhoff, Frederik Marvin; Krampe, Erhard; Böhnke, Birte (adhäsion KLEBEN & DICHTEN)

Spritznieten als neue Organoblech-Metall-Hybridfügetechnik

Stainless steel parts produced by Fused Deposition Modeling and a sintering process compared to components manufactured in Selective Laser Melting - Moritzer, Elmar; Schumacher, C. (4th International Conference Progress on Polymers and Composites Products and Manufacturing Technologies (POLCOM))

Wechseldehnungsschweißen - Entwicklung einer Fügetechnologie für 3D-Geometrien - Vogtschmidt, Sascha; Fiebig, Isabel; Schöppner, Volker (Joining Plastics)

Differences between the recycled carbon fibers especially regarding the product quality, - Malatyali, Hatice; Schöppner, Volker; Behrendt, Alexander; Hoemann, Theresa; Sporkmann, Frederick; Hanselle, Felix (SPE ANTEC)

Wechseldehnungsschweißen - Entwicklung einer Fügetechnologie für 3D-Geometrien - Vogtschmidt, Sascha; Schöppner, Volker (DVS CONGRESS 2020 - Große Schweißtechnische Tagung)

Vibration welding of components with angled areas in the direction of vibration - Vogtschmidt, Sascha; Schöppner, Volker (Welding in the World)

Schweißnahtkennwerte für die lebensdaueroptimierte Bauteilauslegung von hochtemperaturbeständigen Thermoplasten - Vogtschmidt, Sascha; Schöppner, Volker (Joining Plastics)

Antecedents and Performance Consequences of High-Potential Scheme Use - Krebs, Benjamin (Academy of Management Proceedings)

Kunststofftechnik Paderborn: Entwicklung von Scale-Up-Regeln für das quasisimultane Laserdurchstrahlschweißen von Thermoplasten - Arndt, Theresa; Schöppner, Volker (Joining Plastics)

Wenn Regeln Potenziale freisetzen - Arndt, Theresa; Schöppner, Volker (K-Zeitung)

Quasi-Simultaneous Laser Transmission Welding - Arndt, Theresa; Schöppner, Volker (PhotonicsViews)

Modellierung des Wärmetransports in zyklisch durchströmten Wärmeübertragern - Mügge, Nils; Kronberg, Alexander; Glushenkov, Maxim; Kenig, Eugeny (Jahrestreffen der ProcessNet-Fachgruppe „Energieverfahrenstechnik“)

Influence of Material Degradation on Weld Seam Quality in Hot Gas Welding of Polyamides - Schöppner, Volker; Bialaschik, Max (73th Annual Assembly of the International Institute of Welding (IIW))

From filament production to material qualification for the FDM process - Moritzer, Elmar; Wächter, Julian

Interdiffusion in aluminum-steel clad strip - Krivská, Barbora; Šlapáková, Michaela; Kihoulou, Martin; Králík, Rostislav; Bajtošová, Lucia; Cieslar, Miroslav; Grydin, Olexandr; Stolbchenko, Mykhailo; Schaper, Mirko (Proc. 20th Conference of Czech and Slovak Physicists)

Device for twin-roll casting of strips with profiled cross-section - Bondarenko, Serhii; Grydin, Olexandr; Oginskiy, Yosyp; Kuzmina, Olga; Frolov, Yaroslav (Theory and practice of metallurgy)
Goal. This article is devoted to the development of a new method of roll-crystallizers profiling for twin-roll casting in order to provide the possibility of manufacturing strips with variable geometry on width as one of the more widely used products in the world. Method. The proposed method of profiling is implemented by using profiling strips that cover one or both rolls-crystallizers. In this way achieved profiling of the surface of the cylindrical internally water-cooled rolls, which corresponds to the desired type of strips profiled cross-section. Research results. For the practical implementation of the proposed profiling method was developed device for twin-roll of strips with profiled cross- section. In this paper presented the basic scheme of developed device for twin-roll casting of strips with profiled cross-section using endless strips and given the principle of operation of developed device for profiling. Scientific novelty. A feature of the developed device is its universality, which provides the possibility of synchronous rotation of tension, profiled and compensating-tension rollers in perpendicular plane to the axis of rotation of the rolls-crystallizers. This implementation of the device for twin-roll casting allows to manufacture different types of strips with profiled cross-section. Practical significance. For developed device for twin-roll casting of strips with profiled cross-section has been obtained patent for the invention of Ukraine. For further practical implementation of the developed device, considering the adjustments that provide practical implementation on a specific laboratory twin-roll casting unit, the device of twin-roll casting of strips with profiled cross-section was designed. In the work are presented the basic structural elements and their appearance in the form of three-dimensional models.

Aluminum-steel clad material prepared by twin-roll casting - KŘIVSKÁ, Barbora; ŠLAPÁKOVÁ, Michaela; Grydin, Olexandr; CIESLAR, Miroslav (METAL 2020 Conference Proeedings)

Deformation of expanded steel mesh inlay inside aluminum matrix during the roll bonding - Frolov, Yaroslav; Haranich, Yurii; Bobukh, Olexandr; Remez, Oleg; Voswinkel, Dietrich; Grydin, Olexandr (Journal of Manufacturing Processes)

Cold rolling of pre-profiled strips from aluminum alloy EN AW-1050 - Bondarenko, Serhii; Grydin, Olexandr; Frolov, Yaroslav; Kuzmina, Olga; Bobukh, Olexandr (Modern Problems of Metallurgy – Scientific Bulletin)

Large-scale heat pumps: Uptake and performance modelling of market-available devices - Jesper, Mateo; Schlosser, Florian; Pag, Felix; Walmsley, Timothy Gordon; Schmitt, Bastian; Vajen, Klaus (Renewable and Sustainable Energy Reviews)

Heat Pump Bridge Analysis Using the Modified Energy Transfer Diagram - Schlosser, Florian; Wiebe, Heinrich; Walmsley, Timothy G.; Atkins, Martin J.; Walmsley, Michael R. W.; Hesselbach, Jens (Energies)
Heat pumps are the key technology to decarbonise thermal processes by upgrading industrial surplus heat using renewable electricity. Existing insight-based integration methods refer to the idealised Grand Composite Curve requiring the full exploitation of heat recovery potential but leave the question of how to deal with technical or economic limitations unanswered. In this work, a novel Heat Pump Bridge Analysis (HPBA) is introduced for practically targeting technical and economic heat pump potential by applying Coefficient of Performance curves into the Modified Energy Transfer Diagram (METD). Removing cross-Pinch violations and operating heat exchangers at minimum approach temperatures by combined application of Bridge Analysis increases the heat recovery rate and reduce the temperature lift to be pumped at the same time. The insight-based METD allows the individual matching of heat surpluses and deficits of individual streams with the capabilities and performance of different market-available heat pump concepts. For an illustrative example, the presented modifications based on HPBA increase the economically viable share of the technical heat pump potential from 61% to 79%.

Large-scale heat pumps: Applications, performance, economic feasibility and industrial integration - Schlosser, F.; Jesper, M.; Vogelsang, J.; Walmsley, T.G.; Arpagaus, C.; Hesselbach, J. (Renewable and Sustainable Energy Reviews)

Kombination und Integration etablierter Technologien mit additiven Fertigungsverfahren - Lieneke, Tobias; Künneke, Thomas; Eschner, Niclas; Jacob, Alexander; Schäfer, Martin; Hickmann, Thorsten; Faroun, Rami; Hoffmann, Markus; Scholl, Markus; Baumeister, Kai; Zimmer, Detmar; Lanza, Gisela

Transfer und Kooperation im regionalen Kontext. Erfahrungen aus der Forschung zu kommunalem Bildungsmanagement - Peter F. E. Sloane, Dieter Euler, Tobias Jenert (Berufsbildung in Wissenschaft und Praxis)

Neuartige Fügetechnik für Organoblech-Hybridverbindungen

Spritznieten als neue Organoblech-Metall-Hybridfügetechnik

Pre-seasonal Assessment and Performance Diagnostics: Orthopaedic and Functional Aspects - Gokeler, Alli; Büchel, Daniel (Injury and Health Risk Management in Sports)

Peer Mentoring an der Fakultät für Wirtschaftswissenschaften - Konzept und Realisierungsformen - Sloane, Hannah; Kremer, H.-Hugo (Mentoring in Hochschuldidaktik und -praxis - Eine Reflexion wissenschaftlicher Erkenntnisse und praktischer Erfahrungen)

Interferometric method for determining the losses of spatially multi-mode nonlinear waveguides based on second harmonic generation - Santandrea, Matteo; Stefszky, Michael; Roeland, Ganaël; Silberhorn, Christine (Optics Express)

Experimental control of the degree of non-classicality via quantum coherence - Smirne, A; Nitsche, T; Egloff, D; Barkhofen, Sonja; De, S; Dhand, I; Silberhorn, Christine; Huelga, S F; Plenio, M B (Quantum Science and Technology)

Long‐term effects of hydrolyzed formulae on atopic diseases in the GINI study - Gappa, Monika; Filipiak‐Pittroff, Birgit; Libuda, Lars; Berg, Andrea; Koletzko, Sibylle; Bauer, Carl‐Peter; Heinrich, Joachim; Schikowski, Tamara; Berdel, Dietrich; Standl, Marie (Allergy)

A mendelian randomization study on causal effects of 25(OH)vitamin D levels on attention deficit/hyperactivity disorder - Libuda, Lars; Naaresh, Roaa; Ludwig, Christine; Laabs, Björn-Hergen; Antel, Jochen; Föcker, Manuel; Hebebrand, Johannes; Hinney, Anke; Peters, Triinu (European Journal of Nutrition)
Abstract Background While observational studies revealed an inverse association between serum 25(OH)vitamin D (25(OH)D) and the risk of attention deficit/hyperactivity disorder (ADHD), the causality of this relationship remains unclear. Methods We conducted a bidirectional two-sample Mendelian Randomization (MR) study to examine whether 25(OH)D has an effect on the risk to develop ADHD or vice versa. Information on single nucleotide polymorphisms (SNP) associated with serum 25(OH)D was obtained from a genome-wide association study (GWAS) considering phenotype data from 79,366 individuals of European ancestry. Data on risk for ADHD were derived from a GWAS analysis with 20,183 individuals diagnosed with ADHD and 35,191 controls. For our analysis, we considered effect sizes based on the European participants (19,099 cases and 34,194 controls). Results Single SNP analyses showed a causal effect of vitamin D on ADHD risk for only one SNP (rs12785878, p = 0.024). The overall MR estimates did not reveal a causal effect of 25(OH)D on risk for ADHD. In the reverse analysis, neither any single nor the multi-SNP MR analyses showed a causal effect of ADHD on 25(OH)D. Conclusion Results from this two-sample MR study did not confirm a causal effect of 25(OH)D on ADHD or vice versa. Accordingly, our study does not provide evidence that improving 25(OH)D via supplementation could reduce the risk of developing ADHD.

The overall diet quality in childhood is prospectively associated with the timing of puberty - Duan, Ruonan; Qiao, Tian; Chen, Yue; Chen, Mengxue; Xue, Hongmei; Zhou, Xue; Yang, Mingzhe; Liu, Yan; Zhao, Li; Libuda, Lars; Cheng, Guo (European Journal of Nutrition)
Abstract Purpose The influences of nutrition in childhood on puberty onset could have sustained consequences for health and wellbeing later in life. The aim of this study was to investigate the prospective association of diet quality prior to puberty with the timing of puberty onset. Methods We considered data from 3983 SCCNG (Southwest China Childhood Nutrition and Growth) study participants with dietary data, anthropometric measurement, and information on potential confounders at their baseline assessment (mean age: 7.1 years for girls and 7.3 years for boys; mean length of follow-up was 4.2 years). Cox proportional hazard regression estimating hazard ratios (HRs) and 95% confidence intervals (CIs) were used to examine the relationship between diet quality and puberty onset. Dietary intake at baseline was assessed using a validated food frequency questionnaire. Diet quality was determined using the Chinese Children Dietary Index (CCDI) which measures adherence to current dietary recommendations (theoretical range: 0–160 points). Age at Tanner stage 2 for breast/genital development (B2/G2), menarche or voice break (M/VB) were used as pubertal markers. Results The CCDI score ranged from 56.2 to 136.3 for girls and 46.1–131.5 for boys. Pubertal markers consistently indicate that girls and boys with higher diet quality were more likely to enter their puberty later than their counterparts with lower CCDI scores (higher vs. lower CCDI tertiles: adjusted HR for age at B2: 0.85 (95% CI, 0.81–0.94), p for trend = 0.02; G2: 0.86 (95% CI,0.80–0.96), p for trend = 0.02; M: 0.86 (95% CI,0.80–0.95), p for trend = 0.02; VB: 0.86 (95% CI,0.79–0.98), p for trend = 0.03), after adjustment for paternal education level, baseline energy intake, and pre-pubertal body fat. Conclusions Our data suggested a later puberty onset and later timing of progressed puberty stages in children with a high diet quality, which were independent of pre-pubertal body fat.

Qualifizierung von Studierenden des Grund- und Förderschullehramts für den inklusiven Unterricht in der Grundschule - Franzen, Katja; Görel, Gamze; Hellmich, Frank; Filipiak, Agnes; Albers, Timm (Sonderpädagogik und Bildungsforschung – Fremde Schwestern?)

School-based interventions to support student participation. A comparison of different programs. Results from the FRIEND-SHIP project - Hassani, Sepideh; Aroni, Katerina; Schwab, Susanne; Resch, Katharina; Toulia, Anastasia; Alves, Silvia; Görel, Gamze; Löper, Marwin Felix; Avramidis, Elias; Silveira- Maia, Mónica; Sanches-Ferreira, Manuela; Hellmich, Frank

Unterschiede in den Einstellungen zur Teamarbeit im inklusiven Unterricht zwischen Studierenden des Grund- und Förderschullehramts - Hoya, Fabian Karl; Schulze, Jan Roland; Hellmich, Frank (Sonderpädagogik und Bildungsforschung – Fremde Schwestern?)

Expertiseentwicklung: Umwandlung von Wissen in Können - Harteis, Christian; Billett, Stephen; Gruber, Hans (Implizites Wissen. Berufs- und wirtschaftspädagogische Annäherungen)

Einstellungen von Kindern gegenüber Peers mit Förderbedarf: Die Rolle persönlicher Ressourcen für die soziale Partizipation. - Löper, Marwin Felix

Determinanten für die Einstellungen von Grundschulkindern gegenüber Peers mit einem sonderpädagogischen Förderbedarf in der emotionalen und sozialen Entwicklung - Löper, Marwin Felix; Hellmich, Frank (Sonderpädagogik und Bildungsforschung – Fremde Schwestern?)

Die Ernährungsversorgung in Familien zwischen Zeit, Alltag und Haushaltsführung. Eine Mixed-Methods-Untersuchung - Klünder, Nina

Der Jugendamts-Monitor. Aufgaben – Trends – Daten - Müller, Heinz; Klünder, Nina

Optimal and Greedy Heuristic Approaches for Scheduling and Mapping of Hardware Tasks to Reconfigurable Computing Devices - Guetttatfi, Zakarya; Kaufmann, Paul; Platzner, Marco (Proceedings of the International Workshop on Applied Reconfigurable Computing (ARC))

Intrinsic Quality Assessment of Arguments - Wachsmuth, Henning; Werner, Till (Proceedings of COLING 2020, the 28th International Conference on Computational Linguistics)

Analyzing the Persuasive Effect of Style in News Editorial Argumentation - El Baff, Roxanne; Wachsmuth, Henning; Al-Khatib, Khalid; Stein, Benno (Proceedings of 58th Annual Meeting of the Association for Computational Linguistics)

Schule zeitgemäß leiten – Perspektiven für die Schulleitungsqualifizierung in einer digitalisierten Welt - Fugmann, Martin; Eickelmann, Birgit; Neubauer, Daniel (Digitalisierung – Neue Aufgaben der Schulleitung)

Lehrkräfte in der digitalisierten Welt. Orientierungsrahmen für die Lehrerausbildung und Lehrerfortbildung in NRW - Eickelmann, Birgit

Die Perspektive der Schülerinnen und Schüler auf ihre digitale Zukunft. Ergebnisse der Studie ICILS 2018 - Eickelmann, Birgit; Labusch, Amelie (Friedrich Jahresheft 2020 #schuleDIGITAL)

Zukunftsfähige Schulentwicklung in der digitalisierten Welt. Qualität und Nachhaltigkeit als Erfolgsfaktoren - Eickelmann, Birgit (Friedrich Jahresheft #schuleDIGITAL)

Digitale Bildung (Friedrich Jahresheft #schuleDIGITAL)

ICILS 2018 – Wo steht Deutschland im internationalen Vergleich? - Eickelmann, Birgit (Friedrich Jahresheft #schuleDIGITAL)

Ergebnisse der ICILS-2018-Studie. Unterrichtliche Nutzung digitaler Medien in Deutschland im internationalen Vergleich und zukunftsfähige Perspektiven - Eickelmann, Birgit (Zeitschrift Schulmanagement. Fachzeitschrift für Schul- und Unterrichtsentwicklung)

Relevanz schulischer Medienkonzepte als Orientierung für die Schule im Zuge der fortschreitenden Digitalisierung - Heldt, Melanie; Lorenz, Ramona; Eickelmann, Birgit (Unterrichtswissenschaft)
Zusammenfassung Für Schulen sind Orientierungen in der digitalen Welt angesichts neuer Herausforderungen durch die Digitalisierung von steigender Relevanz. Ein zentrales Instrument stellen dabei schulische Medienkonzepte dar, die gemeinsam vereinbarte Orientierungen für die schulische Arbeit und Schulentwicklungsprozesse enthalten. Zudem stellt die Medienkonzeptentwicklung einen Bestandteil theoretischer Modelle zur Erfassung und Beschreibung von Qualitätsdimensionen schulischer Medienbildung dar. Vor diesem Hintergrund untersucht der vorliegende Beitrag (1) die Relevanz von Medienkonzepten aus der Sicht von Schulleitungen und Schulträgern. Außerdem wird beleuchtet, (2) welche Personengruppen an den Schulen für Aufgaben im Kontext des Medienkonzeptes zuständig sind und (3) ob signifikante Unterschiede der schulischen Rahmenbedingungen, des Schulleitungshandelns und des Support je nach Vorhandensein eines Medienkonzeptes vorzufinden sind. Die Fragestellungen werden explorativ auf Grundlage der triangulativ angelegten Untersuchung des technischen und pädagogischen Supports an Schulen bearbeitet, in deren Rahmen N = 601 Lehrkräfte der Sekundarstufe I befragt wurden. Zudem wurden Interviews mit N = 8 Schulleitungen sowie N = 14 Schulträgern, die jeweils möglichst weit im Digitalisierungsprozess vorangeschritten sind, geführt und inhaltsanalytisch ausgewertet. Im Ergebnis zeigt sich, dass die Relevanz von Medienkonzepten für eine gelingende Schulentwicklung mit digitalen Medien als hoch eingeschätzt wird. Des Weiteren wird ersichtlich, dass die in den Einzelschulen für Belange der Medienkonzeptentwicklung zuständigen Akteursgruppen vielfältig zusammengesetzt sind. Ferner können bedeutsame Unterschiede im Hinblick auf die untersuchten Indikatoren je nach Vorhandensein eines Medienkonzeptes aufgezeigt werden. Die Arbeit mit Medienkonzepten kann somit das Herzstück der Schulentwicklung im Kontext der Digitalisierung darstellen.

Wie der Blick in die Zahlen für den Blick nach vorne hilft. Perspektiven aus der Studie ICILS 2018 in der Zeit der Corona-Krise und darüber hinaus - Eickelmann, Birgit (Lehren & Lernen. Zeitschrift für Schule und Innovation aus Baden-Württemberg. Sonderausgabe 'Lernen in Zeiten der Schulschließungen')

Die Supportsituation an Schulen der Sekundarstufe I in Deutschland – Wunsch und Wirklichkeit - Heldt, Melanie; Lorenz, Ramona; Endberg, Manuela; Eickelmann, Birgit (SchulVerwaltung NRW. Fachzeitschrift für Schulentwicklung und Schulmanagement)

Schul- und Unterrichtsentwicklung unter digitalen Bedingungen – empirische Befunde und notwendige Schwerpunktsetzungen - Eickelmann, Birgit

ICILS 2018-NRW. Zentrale Ergebnisse und Perspektiven für die Entwicklung schulischer Digitalisierungsprozesse in Nordrhein-Westfalen - Eickelmann, Birgit; Labusch, Amelie (SchulVerwaltung NRW. Fachzeitschrift für Schulentwicklung und Schulmanagement)

Lernen mit digitalen Medien. Zielsetzungen in Zeiten von Corona und unter besonderer Berücksichtigung von sozialen Ungleichheiten - Eickelmann, Birgit; Gerick, Julia ("Langsam vermisse ich die Schule...". Schule während und nach der Corona Pandemie)
Die Herausforderung, schulisches Lernen in Zeiten der Corona-Pandemie zu re-organisieren, hat einen neuen Blick auf die Potenziale und Notwendigkeiten des Lernens mit digitalen Medien eröffnet. Die Diskussion erstreckt sich von Euphorie und beobachtbaren Innovationsschüben bis hin zu Ernüchterung über tatsächliche Praktiken, fehlende Rahmenbedingungen und Fragen der Bildungsgerechtigkeit. Vor diesem Hintergrund werden im vorliegenden Beitrag die Zielsetzungen schulischen Lernens mit digitalen Medien ausdifferenziert. (DIPF/Orig.)

Schule in Zeiten der Pandemie. Empfehlungen für die Gestaltung des Schuljahres 2020/21 - Expert*innenkommission der Friedrich-Ebert-Stiftung, D

Die drei zentralen Herausforderungen für den Bildungsbereich mit der Perspektive auf zukünftige Entwicklungen - Eickelmann, Birgit (Digitale Bildung nach Corona)

Nachhaltiger Digitalisierungsschub im Schulbereich und in der Lehrkräftebildung durch die Pandemie? – Schön wär’s - Eickelmann, Birgit

Strukturelle Rahmenbedingung der Digitalisierung im Schulbereich in NRW – neue Forschungsbefunde und mögliche Perspektiven für nachhaltig wirksame Entwicklungen - Eickelmann, Birgit (BildungsImpulseRuhr)

Lehrerbildung und Digitalisierung. Ein empirischer Blick auf der Grundlage der Studie ICILS 2018 - Gerick, Julia; Eickelmann, Birgit (Beiträge zur Lehrerbildung und Bildungsforschung. Digital?! Perspektiven der Digitalisierung für den Lehrerberuf und die Lehrerbildung)

Students’ computer literacy and the use of tablets in upper secondary schools - Eickelmann, Birgit; Drossel, Kerstin (Encyclopedia of Education and Information Technologies)

Computational thinking competences in countries from three different continents in the mirror of students' characteristics and school learning - Labusch, Amelie; Eickelmann, Birgit (Proceedings of International Conference on Computational Thinking Education 2020)

Modellschulen ‚Lernen mit digitalen Medien‘ in der Pandemie-Zeit – Gestaltungsansätze und Lessons Learnt - Gerick, Julia; Eickelmann, Birgit; Steglich, Emilie (Fachzeitschrift für Schul- und Unterrichtsentwicklung)

Sozial- und migrationsbedingte Disparitäten im Bereich ‚Computational Thinking‘ von Schülerinnen und Schülern - Labusch, Amelie; Vennemann, Mario; Eickelmann, Birgit (ICILS 2018 #NRW. Vertiefende Analysen und Befunde für Nordrhein-Westfalen im internationalen Vergleich)

Kompetenzen im Bereich ‚Computational Thinking‘ von Schülerinnen und Schülern im internationalen Vergleich - Labusch, Amelie; Eickelmann, Birgit; Vahrenhold, Jan; Vennemann, Mario (ICILS 2018 #NRW. Vertiefende Analysen und Befunde für Nordrhein-Westfalen im internationalen Vergleich)

Die Nutzung digitaler Medien aus der Perspektive der Schülerinnen und Schüler - Vennemann, Mario; Labusch, Amelie; Eickelmann, Birgit (ICILS 2018 #NRW. Vertiefende Analysen und Befunde für Nordrhein-Westfalen im internationalen Vergleich)

Der Informatikunterricht aus Sicht schulischer Akteurinnen und Akteure – Analysen und Perspektiven - Vahrenhold, Jan; Vennemann, Mario; Labusch, Amelie; Eickelmann, Birgit (ICILS 2018 #NRW. Vertiefende Analysen und Befunde für Nordrhein-Westfalen im internationalen Vergleich)

Rolle des schulischen Ganztags für das Lernen mit digitalen Medien - Eickelmann, Birgit; Heldt, Melanie; Port, Sonja (ICILS 2018 #NRW. Vertiefende Analysen und Befunde für Nordrhein-Westfalen im internationalen Vergleich)

Konzeptionelle Verankerung digitaler Medien in schulisches Lernen und Lehren - Heldt, Melanie; Labusch, Amelie; Eickelmann, Birgit; Port, Sonja (ICILS 2018 #NRW. Vertiefende Analysen und Befunde für Nordrhein-Westfalen im internationalen Vergleich)

Modellschulen ‚Lernen mit digitalen Medien‘ in der Pandemie-Zeit – Gestaltungsansätze und Lessons Learnt - Gerick, Julia; Eickelmann, Birgit; Steglich, Emilie (SchulManagement. Fachzeitschrift für Schul- und Unterrichtsentwicklung)

Schulleitung und Digitalisierung. Fünf Thesen - Eickelmann, Birgit (SchulManagement. Fachzeitschrift für Schul- und Unterrichtsentwicklung)

Ergebnisse der wissenschaftlichen Begleitung der Evaluation des Projekts ‚Lernen mit digitalen Medien‘ an den Förderzentren Geistige Entwicklung/Körperliche und motorische Entwicklung in Schleswig-Holstein ergänzt um eine Vertiefungsuntersuchung im Kontext des Lernens mit digitalen Medien unter Pandemie-Bedingungen - Gerick, Julia; Eickelmann, Birgit; Steglich, Emilie

Ergebnisse der vertiefenden Untersuchung der Modellschulen ‚Lernen mit digitalen Medien‘ (Phase III) in Schleswig-Holstein mit Fokus auf der Gestaltung von Schule in der Zeit der Corona-Pandemie - Gerick, Julia; Eickelmann, Birgit

Ergebnisse der wissenschaftlichen Begleitung der Evaluation der dritten Phase des Projekts ‚Lernen mit digitalen Medien‘ mit dem Schwerpunkt auf digitalen Medien im Fachunterricht an Modellschulen in Schleswig-Holstein - Gerick, Julia; Eickelmann, Birgit

Re-Definition der digitalisierungsbezogenen Schulleitungsfunktionen in der Pandemie-Zeit. Plan BD #02 Leadership - Eickelmann, Birgit (Fachmagazin für Schule in der digitalen Welt)

Digitalisierungsbezogene Professionalisierung von Lehrpersonen. Befunde zu Aktivitäten, Gelegenheiten und schulischen Prioritäten aus ICILS 2013 und ICILS 2018 im Vergleich - Gerick, Julia; Eickelmann, Birgit; Vennemann, Mario (Journal für Schulentwicklung)

Fortbildung im digitalen Zeitalter (Journal für Schulentwicklung)

Der digitale Fußabdruck, Schatten oder Zwilling von Maschinen und Menschen - Engels, Gregor (Gruppe. Interaktion. Organisation. Zeitschrift für Angewandte Organisationspsychologie (GIO))

Annette-von-Droste-Hülshoff-Preis 2020 Michael Roes im Gespräch mit LWL-Direktor Matthias Löb und Prof. Dr. Norbert Otto Eke, - Eke, Norbert (www.literaturkommission.lwl.org/media/filer_public/cb/ad/cbad76c2-23ac-4cb1-ade3-883dcbd1bbf0/broschure_roes_210x210.pdf)

[zu:] Cristina Rossi: Sinn und Struktur. Zugänge zu den Collagen Herta Müllers. Würzburg: Königshausen & Neumann, 2019 - Eke, Norbert (Literaturwissenschaftliches Jahrbuch)

Dietary flavonoids among children and adolescents in the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study: intake, food sources and trends from 1985 until 2016 - Rienks, Johanna; Penczynski, Katharina J.; Schmitting, Sarah; Buyken, Anette; Nöthlings, Ute (British Journal of Nutrition)
Abstract Flavonoids are suggested to reduce disease risk. Since dietary habits are acquired during early life, describing age and time trends of flavonoid intake and major food sources are important for monitoring and disease prevention in later life. We aimed to describe total flavonoid intake and food sources and to investigate age and time trends of flavonoid intake in 3–18-year-olds, from the Dortmund Nutritional and Anthropometric Longitudinally Designed study from 1985 to 2016. Intake was assessed annually using 3-d weighed food records (WFR). Flavonoid values were assigned using the United States Department of Agriculture database. Foods contributing to intake were determined. Age and time trends in total flavonoid and isoflavone density were analysed by sex with PROC MIXED. In total, 1312 children completed 10 758 WFR. Across all ages, daily mean total flavonoid density was lower in boys compared with girls (134 v . 146 mg/4184 kJ) and no difference in median isoflavone density (0·04 mg/4184 kJ per d) was found. The top five foods contributing to total flavonoid intake were apple with peel (15·0/17·1 %), strawberries (5·9/6·1 %), chocolate spread (3·9/3·5 %), orange juice (3·5/3·4 %) and pasta (3·5/3·4 %) for boys and girls, respectively. Overall, in boys, total flavonoid density decreased over the course of age and time. In girls, there was no association with age or time. In both sexes, isoflavone density followed a U-shaped age trend with no change over time. From a public health perspective, the overall observed downwards trend of flavonoid intake in boys deserves attention. Future initiatives should be tailored at maintaining a high flavonoid density as children age, specifically among boys.

Short-term metreleptin treatment of patients with anorexia nervosa: rapid on-set of beneficial cognitive, emotional, and behavioral effects - Milos, Gabriella; Antel, Jochen; Kaufmann, Lisa-Katrin; Barth, Nikolaus; Koller, Antonia; Tan, Susanne; Wiesing, Urban; Hinney, Anke; Libuda, Lars; Wabitsch, Martin; von Känel, Roland; Hebebrand, Johannes (Translational Psychiatry)
Abstract To examine the hypothesis that normalization of low circulating leptin levels in patients with anorexia nervosa ameliorates hyperactivity, three seriously ill females with hyperactivity were treated off-label with metreleptin (recombinant human leptin) for up to 14 days. Drive for activity, repetitive thoughts of food, inner restlessness, and weight phobia decreased in two patients. Surprisingly, depression improved rapidly in all patients. No serious adverse events occurred. Due to obvious limitations of uncontrolled case series, placebo-controlled clinical trials are mandatory to confirm the observed rapid onset of beneficial effects. Our findings suggest an important role of hypoleptinemia in the mental and behavioral phenotype of anorexia nervosa.

The Role of Genetic Variation of BMI, Body Composition, and Fat Distribution for Mental Traits and Disorders: A Look-Up and Mendelian Randomization Study - Peters, Triinu; Nüllig, Lena; Antel, Jochen; Naaresh, Roaa; Laabs, Björn-Hergen; Tegeler, Lisa; Amhaouach, Chaima; Libuda, Lars; Hinney, Anke; Hebebrand, Johannes (Frontiers in Genetics)

Shortest Paths in a Hybrid Network Model - Augustine, John; Hinnenthal, Kristian; Kuhn, Fabian; Scheideler, Christian; Schneider, Philipp (Proceedings of the 2020 ACM-SIAM Symposium on Discrete Algorithms, SODA 2020, Salt Lake City, UT, USA, January 5-8, 2020)

Systematische Entwicklung von Normstrategien für Smart Services - Koldewey, Christian; Frank, Maximilian; Gausemeier, Jürgen; Bäsecke, Alexander; Chohan, Nadia; Reinhold, Jannik (ZWF, Zeitschrift für wirtschaftliche Fabrikplanung 115(7-8))
Die Verfügbarkeit von Daten aus dem Betrieb hat durch die Einführung von vernetzten intelligenten Fertigungssystemen (cyber-physische Systeme) stark zugenommen. Hieraus eröffnen sich Erfolg versprechende Möglichkeiten für Smart Services und damit verbundene neue Geschäftsfelder. Voraussetzung für den Eintritt in ein neues Geschäft mit Smart Services ist eine fundierte Geschäftsstrategie. Wir zeigen die zentralen Gestaltungsfelder von Smart Service-Strategien auf und erläutern, wie sechs von uns ermittelte Normstrategien bei der Formulierung einer attraktiven Strategie helfen können.

Strategische Planung - Gausemeier, Jürgen; Eckelt, Daniel; Dülme, Christian (Handbuch Gestaltung digitaler und vernetzter Arbeitswelten)

Framework and Functionality Patterns for Smart Service Innovation - Koldewey, Christian; Meyer, Maurice; Stockbruegger, Patrick; Dumitrescu, Roman; Gausemeier, Jürgen (Procedia CIRP (91))

Developing Strategies for Digital Transformation in SMEs with Maturity Models - Pierenkemper, Christoph; Gausemeier, Jürgen (Proceeding of the ISPIM Connects, 1. - 4. Mrz. 2020)

Pattern‐based development of digital platforms - Drewel, Marvin; Özcan, Leon; Koldewey, Christian; Gausemeier, Jürgen (Creativity and Innovation Management)

Mechanical and mathematical model of a caterpillar drive with a triangular contour for solving problems of vertical dynamics of a tracked vehicle - Poddubnyi, Vladimir I.; Trächtler, Ansgar; Warkentin, Andreas; Henke, Christian (Vestnik Mashinostroeniya)

Integrating Score Rendition in the MEI Garage - Rettinghaus, Klaus; Röwenstrunk, Daniel; Kepper, Johannes

Die Einstellung angehender Lehrkräfte zu Forschendem Lernen im Praxissemester und Referendariat - Homt, Martina; Bloh, Bea; Grosser, Christine (Forschendes Lernen in der Lehrer/innenbildung. Implikationen für Wissenschaft und Praxis)

Early changes in hepatic energy metabolism and lipid content in recent-onset type 1 and 2 diabetes mellitus - Kupriyanova, Yuliya; Zaharia, Oana Patricia; Bobrov, Pavel; Karusheva, Yanislava; Burkart, Volker; Szendroedi, Julia; Hwang, Jong-Hee; Roden, Michael; Roden, M.; Al-Hasani, H.; Burkart, V.; Buyken, Anette; et al. (Journal of Hepatology)

World trends in sugar-sweetened beverage and dietary sugar intakes in children and adolescents: a systematic review - Della Corte, Karen; Fife, Jessica; Gardner, Alexis; Murphy, Britta L; Kleis, Linda; Della Corte, Dennis; Schwingshackl, Lukas; LeCheminant, James D; Buyken, Anette (Nutrition Reviews)
Abstract Objective To provide a systematic overview of world dietary sugar and sugar-sweetened beverage (SSB) intake trends in children and adolescents. Data Sources Medline, Embase, and the Cochrane Central Register of Controlled Trials in the Cochrane Library were searched through January 2019 to identify longitudinal follow-up studies with time-trend data and repeated cross-sectional studies. Data Extraction Data from studies reporting ≥ 2 measurements (sugars, SSB, or sweets/candy) over ≥ 2 years and included ≥ 20 healthy, normal- or overweight children or adolescents aged 1–19 years. Data Analysis Data from 43 articles (n = 4 prospective cohort studies; n = 39 repeated cross-sectional studies) from 15 countries (n = 8 European countries plus Australia, Canada, China, South Korea, Mexico, Russia, and the United States) are presented narratively. According to the risk of bias in nonrandomized studies of interventions tool, 34 studies were judged to have a moderate risk of bias, and 5 to have a serious risk of bias. Conclusions Consumption among US children and adolescents increased substantially in the decades preceding 2000, followed by a faster and continued decline. As a whole, other international intake trends did not reveal drastic increases and decreases in SSB and dietary sugars; they tended to change only slightly across 3 decades.

Dietary Fibre Consensus from the International Carbohydrate Quality Consortium (ICQC) - Augustin, Livia S. A.; Aas, Anne-Marie; Astrup, Arnie; Atkinson, Fiona S.; Baer-Sinnott, Sara; Barclay, Alan W.; Brand-Miller, Jennie C.; Brighenti, Furio; Bullo, Monica; Buyken, Anette; Ceriello, Antonio; Ellis, Peter R.; et al. (Nutrients)
Dietary fibre is a generic term describing non-absorbed plant carbohydrates and small amounts of associated non-carbohydrate components. The main contributors of fibre to the diet are the cell walls of plant tissues, which are supramolecular polymer networks containing variable proportions of cellulose, hemicelluloses, pectic substances, and non-carbohydrate components, such as lignin. Other contributors of fibre are the intracellular storage oligosaccharides, such as fructans. A distinction needs to be made between intrinsic sources of dietary fibre and purified forms of fibre, given that the three-dimensional matrix of the plant cell wall confers benefits beyond fibre isolates. Movement through the digestive tract modifies the cell wall structure and may affect the interactions with the colonic microbes (e.g., small intestinally non-absorbed carbohydrates are broken down by bacteria to short-chain fatty acids, absorbed by colonocytes). These aspects, combined with the fibre associated components (e.g., micronutrients, polyphenols, phytosterols, and phytoestrogens), may contribute to the health outcomes seen with the consumption of dietary fibre. Therefore, where possible, processing should minimise the degradation of the plant cell wall structures to preserve some of its benefits. Food labelling should include dietary fibre values and distinguish between intrinsic and added fibre. Labelling may also help achieve the recommended intake of 14 g/1000 kcal/day.

Inflammatory mediators in the adipo-renal axis: leptin, adiponectin, and soluble ICAM-1 - Hua, Yifan; Herder, Christian; Kalhoff, Hermann; Buyken, Anette; Esche, Jonas; Krupp, Danika; Wudy, Stefan A.; Remer, Thomas (American Journal of Physiology-Renal Physiology)
A lower 24-h urine pH (24h-pH), i.e., a higher renal excretion of free protons, at a given acid load to the body, denotes a reduction in the kidney’s capacity for net acid excretion (NAE). There is increasing evidence, not only for patients with type 2 diabetes but also for healthy individuals, that higher body fatness or waist circumference (WC) has a negative impact on renal function to excrete acids (NAE). We hypothesized that adiposity-related inflammation molecules might mediate this relation between adiposity and renal acid excretion function. Twelve biomarkers of inflammation were measured in fasting blood samples from 162 adult participants (18–25 yr old) of the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study who had undergone anthropometric measurements and collected 24-h urine samples. Both Baron and Kenny’s (B&K’s) steps to test mediation and causal mediation analysis were conducted to examine the potential mediatory roles of biomarkers of inflammation in the WC-24-h pH relationship after strictly controlling for laboratory-measured NAE. In B&K’s mediation analysis, leptin, soluble intercellular adhesion molecule 1 (sICAM-1), and adiponectin significantly associated with the outcome 24-h pH and attenuated the WC-pH relation. In agreement herewith, causal mediation analysis estimated the “natural indirect effects” of WC on 24-h pH via leptin ( P = 0.01) and adiponectin ( P = 0.03) to be significant, with a trend for sICAM-1 ( P = 0.09). The calculated proportions mediated by leptin, adiponectin, and sICAM-1 were 64%, 23%, and 12%, respectively. Both mediation analyses identified an inflammatory cytokine (leptin) and an anti-inflammatory cytokine (adiponectin) along with sICAM-1 as being potentially involved in mediating adiposity-related influences on renal acid excretion capacity.